2005
DOI: 10.1577/h03-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variation of Early Mortality Syndrome in Salmonids from Lakes Michigan and Huron

Abstract: To assess the extent that early mortality syndrome (EMS) impacts different Pacific salmonid stocks and the association of EMS with thiamine, we collected eggs of coho salmon Oncorhynchus kisutch from three Lake Michigan tributaries (Platte River, Thompson Creek, and Root River) in 1996-2001. We also obtained eggs of Chinook salmon O. tshawytscha from Lake Michigan (Little Manistee River) and Lake Huron (Swan River) in 1998-2001. Unfertilized eggs from individual females were frozen for thiamine analysis, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 11 publications
4
39
1
Order By: Relevance
“…These relatively low levels may not be lethal, but lower thiamine levels can impact adult fish neurological function [19,45], metabolic rates [15,28], and muscle weakness [34], thereby potentially decreasing foraging efficiency and subsequently contributing to smaller body sizes [22,28]. Similar to that reported by other authors [14,17,30,46], free thiamine was the most prevalent form of thiamine in Lake Oahe Chinook Salmon eggs. Free thiamine likely acts as a storage vitamer and is converted to TPP or TMP later during development [46].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These relatively low levels may not be lethal, but lower thiamine levels can impact adult fish neurological function [19,45], metabolic rates [15,28], and muscle weakness [34], thereby potentially decreasing foraging efficiency and subsequently contributing to smaller body sizes [22,28]. Similar to that reported by other authors [14,17,30,46], free thiamine was the most prevalent form of thiamine in Lake Oahe Chinook Salmon eggs. Free thiamine likely acts as a storage vitamer and is converted to TPP or TMP later during development [46].…”
Section: Discussionsupporting
confidence: 68%
“…Overall, thiamine levels in Chinook Salmon eggs from Lake Oahe are far greater than levels found in the Great Lakes or the Baltic Sea, where thiamine deficiency complex is frequently observed. The minimum total egg thiamine level observed in this study is typical of Chinook Salmon eggs that did not exhibit thiamine deficiency complex from Lakes Michigan and Huron [30]. In Lake Michigan, Lake Huron, and Lake Ontario, mean egg total thiamine levels for Salmonids have been reported as 2.0, 3.1, and 1.3 nmol/g, respectively [32].…”
Section: Discussionmentioning
confidence: 80%
“…Thiamine thresholds for direct mortality vary among fish species, with estimates of egg thiamine thresholds for lake trout, Chinook salmon Oncorhynchus tshawytscha, coho salmon Oncorhynchus kisutch and Atlantic salmon Salmo salar ranging from 0.41 to 2.99 nmol·g −1 (Fisher et al, 1996;Honeyfield et al, 2005;Wolgamood et al, 2005;Werner et al, 2006;Fitzsimons et al, 2007). Rainbow smelt Osmerus mordax larvae hatched from eggs with a mean thiamine content of 2.7 nmol·g −1 showed signs of TDC (Chalupnicki et al, 2010), and walleye embryos from the Maumee River (Lake Erie) showed reduced survival below egg thiamine concentrations of approximately 6 nmol·g −1 (Rinchard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The alewife was found to be one of the most abundant species in the diet of cormorants (Johnson et al 2002). The alewife contains the enzyme thiaminase, which destroys thiamine (vitamin B,, NRC 1983;Ji and Adelman 1998;Fitzsimons et al 2005). Consumption of alewives impairs reproduction in lake trout (Salvelinus namcrycush), coho salmon (Oncorhynchus kisutch), Chinook salmon (Oncorhynchus tshauytscha), rainbow trout (steelhead, Oncorhynchus mykiss), and brown trout (Salmo trutta) (Wolgamood et al 2005;Brown et al 2005;Fitzsimons et al 1999,2005a, 2005b, and 2007, Honeyfield et a1.1998, Homung et al 1998, Brown et al 1998,2005, Marcquenski 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The alewife contains the enzyme thiaminase, which destroys thiamine (vitamin B,, NRC 1983;Ji and Adelman 1998;Fitzsimons et al 2005). Consumption of alewives impairs reproduction in lake trout (Salvelinus namcrycush), coho salmon (Oncorhynchus kisutch), Chinook salmon (Oncorhynchus tshauytscha), rainbow trout (steelhead, Oncorhynchus mykiss), and brown trout (Salmo trutta) (Wolgamood et al 2005;Brown et al 2005;Fitzsimons et al 1999,2005a, 2005b, and 2007, Honeyfield et a1.1998, Homung et al 1998, Brown et al 1998,2005, Marcquenski 1996. When nestling wood storks (Mycleria americana) were fed almost exclusively gizzard shad (Dorosoma cepedianum), a high-thiaminase fish species they developed thiamine deficiency signs including anorexia, weakness and un-coordination, all of which were reversed by vitamin supplementation (Kahl 1962, Miller 1960.…”
Section: Introductionmentioning
confidence: 99%